Application of a new type of mesh density basket in cleaning and disinfection of small dental equipment (新型密纹篮筐在牙科小器械清洗消毒中的应用) - DENG Yanli (邓艳莉); TU Chengyun (徒成云); LI Yanyan (李严严) (中西医结合护理)
Objective To investigate the application value of a new type of mesh density basket in cleaning and disinfection of small dental equipment. Methods Totally 120 root canal files were randomly divided into the observation group and control group, with 120 files in each group. The stainless steel mesh cup was used in cleaning and disinfection of small dental equipment in the control group, while a new type of mesh density basket was used in the observation group. The quality of cleaning was measured, and the sharp instrument injuries were retrospectively analyzed within 1 year. Results The rate of qualified cleaning was 98. 33%(59/60) in the observation group, which was higher than 85. 00%(51/60) in the control group(P<0. 01). In terms of structural performance of small dental equipment after cleaning, a good performance rate of 100 percent was achieved in the observation group, higher than 80. 00%(48/60) in the control group. The occurrence of sharp instrument injuries has dropped form 26 times to 8 time with 1 year after use of new type of mesh density basket. Conclusion The new type of mesh density basket is effective to improve the quality of cleaning small dental equipment, and reduce the risk of injuries caused by sharp instruments. (目的 探讨新型密纹篮筐在牙科小器械清洗中的应用效果。方法 选取120支待清洗消毒的口腔根管锉随机分为观察组和对照组, 各60支。对照组采用不锈钢网状杯装载清洗, 观察组采用新型双层密纹篮筐装载清洗。评估两组清洗质量, 分析新型双层密纹篮筐使用前后1年内锐器伤发生情况。结果 观察组器械清洗合格率为98. 33%(59/60), 高于对照组的85. 00%(51/60), 差异有统计学意义(P<0. 01)。观察组器械清洗后结构性能均完好, 对照组器功能完好率80. 00%(48/60)。新型密纹篮筐使用前1年内科室发生锐器伤26人次, 使用后的1年内仅发生锐器伤8人次, 有效降低了锐器伤发生风险。结论 新型密纹篮筐装载牙科小器械可有效提高器械清洗质量, 降低工作人员锐器伤发生风险。)